A Diversified Spectrometric and Molecular Docking Technique to Biophysical Study of Interaction between Bovine Serum Albumin and Sodium Salt of Risedronic Acid, a Bisphosphonate for Skeletal Disorders - M. Manjushree; Hosakere D. Revanasiddappa (Bioinorganic Chemistry and Applications)
The binding interaction between bovine serum albumin (BSA) and sodium salt of risedronic acid (RSN) was studied by using the FT-IR (Fourier transform infrared), UV-Vis (ultraviolet–visible), fluorescence (emission and synchronous), CD (circular dichroism) spectrometric, and computational (molecular docking) techniques at 289, 297, and 305 K temperatures with physiological buffer of pH 7.40. The conformational and secondary structural changes observed for BSA from CD spectra and by curve fitting procedure were applied to Fourier self-deconvolution in FT-IR spectra. The formation of a BSA-RSN complex was confirmed from UV-Vis spectroscopy. The static type of quenching shown for RSN to BSA was verified from Stern–Volmer and modified Stern–Volmer equations. The binding constant of order 105 was obtained to be confirming that there exists a strong binding interaction between BSA and RSN. Synchronous fluorescence shows that the microenvironment of tryptophan was altered, not tyrosine of BSA; in addition to this, the distance between tryptophan of BSA and RSN was found out from Forster’s theory of nonradiation energy transfer. The interaction between BSA and RSN mainly occurred as a result of hydrogen bonds and van der Waals forces, the process is exothermic and spontaneous, and it was achieved through van ’t Hoff equation. This interaction was affected by the presence of biologically active Fe2+, Ni2+, Ca2+, Mg2+, and Cd2+ ions and was also studied. The subdomain IIIA of BSA involved with RSN interaction was authenticated from molecular docking analysis.